The Alcalar Model, A Quality Of Life Perception: A Comparative Study Of Institutionalized Elderly People - Malveiro, Jorge Andrez; de Jesus, Saul Neves; Rego, Rui (Journal of Tourism, Sustainability and Well-being, 2016)
Summary: A comparative evaluation was carried out of quality of life (QoL) perception in different communitarian residential institutional environments for senior citizens. Method: A cross-sectional comparative study was conducted using a deductive and descriptive statistical method on a sample of 50 senior inhabitants of the retirement village St. Joseph of Alcalar (Alcalar group), 56 senior residents of traditional retirement homes (RSS group) and 52 senior attendees of day care institutions (DCI group). This research comprised two self-applicable questionnaires for elderly citizens, WHOQOL-BREF and WHOQOL-Old PT. We evaluated 158 senior citizens selected from 22 institutions. Results: The QoL levels perceived by the Alcalar retirement village inhabitants were predominantly higher than the QoL levels perceived by the group of RSS residents and the DCI attendees. The trend in QoL results obtained from the Alcalar retirement village inhabitants was not absolute because it was surpassed by the DCI attendees’ results in some (few) areas assessed with both WHOQOL scales. Conclusion: The Alcalar retirement village group globally showed higher levels of quality of life perception than the other two groups of residents and attendees, respectively, from RSSs and DCIs.